172 Junctophilin-2 interacts with the cardiac L-Type voltage-gated calcium channel. (6th June 2015) - Bennett, Hayley J; Davenport, J Bernard; Kitmitto, Ashraf; Webb, Kirsty
Abstract : Background: Excitation contraction (E-C) coupling in cardiac muscle is regulated by the L-type voltage-gated calcium channels (LTCC) within the t-tubules, and surface membrane, and the ryanodine receptors (RyR2) localised to the junctional sarcoplasmic reticulum (jSR). The juxtaposition of the t-tubules and jSR forms a microdomain termed a dyad. It is now widely accepted that junctophilin-2 (JP2) acts as a protein bridge to maintain the dyad geometry. JP2 is anchored in the SR, via its C-terminal transmembrane domain, and is thought to span the cytosol and interact with the plasma membrane thereby constraining the dyad architecture to provide the optimal proximal distance between the LTCCs and RyR2s to facilitate effective calcium induced calcium release for cardiac contraction. More recently, data has emerged to suggest that JP2 has an additional role, influencing E-C coupling through an interaction with RyR2. Furthermore, there is evidence for an association between JP2 and the LTCC in skeletal muscle. However, the region of the LTCC involved in binding to JP2 was not established nor was whether there is an interaction between JP2 and the LTCC in the heart. Methods: We employed yeast-2-hybrid (Y2H) (Hybrigenics) experiments to investigate JP2 binding partners using human heart cDNA library. Domains of the LTCC were expressed as GST-fusion proteins and JP2 full-length and domains were purified from E.coli . Pull-down experiments were employed to investigate the interaction between the JP2 and the LTCC protein domains. Results: Data from Y2H experiments identified the C-terminal region within the ion channel pore of LTCCs as a JP2 binding partner. Therefore, we designed a series of constructs encompassing the C-terminal domain of the Cav1.2 subunit and expressed them as GST-fusion proteins. Employing purified JP2 we showed a direct interaction with the C-terminal tail of Cav 1.2. Furthermore, we determined that the N-terminal portion of JP2 mediates this interaction. We also investigated whether this interaction is Ca 2+ dependent since we have previously reported that JP2 has a cation binding domain. Our experiments revealed that the JP2-Cav 1.2 interaction is independent of [Ca 2+ ]. Conclusion: This study has provided novel data revealing that not only is there a direct interaction between the cardiac LTCC and JP2 but that the binding domains involve the C-terminal region of Cav 1.2 and the N-terminal domain of JP2. Significantly, the Cav 1.2 C-terminal domain binds calmodulin (CaM), both apoCaM and Ca 2+ CaM, regulating both calcium dependent inactivation (CDI) and facilitation (CDF) of the channel. Therefore, our future studies are directed at understanding the significance of JP2 binding, for example whether JP2 influences channel function (CDI/CDF) and/or whether a JP2-Cav 1.2 is important for LTCC localisation to the dyad.